Optimalisasi Kinerja Pegawai: Stres Kerja dan Kualitas Kehidupan Kerja dengan Mediasi Kepuasan Kerja - Dewi Anggraini; M. I. Nasution; Muhammad Andi Prayogi (JURNAL ILMIAH MANAJEMEN & BISNIS, 2023)
Purpose – This research explores the influence of work stress and Quality of Work Life (QWL) on employee performance by considering the mediating role of job satisfaction.Method – The research used a quantitative approach involving a complete census method, with a sampling number of 74 employees of the National Narcotics Agency of North Sumatra Province. Data was collected using a questionnaire to collect numerical information related to research variables. The data analysis method applied is Structural Equation Modeling (SEM) with Partial Least Squares (PLS) as an analysis technique.Finding –  Job stress does not have a significant favourable influence on employee performance but is negatively correlated with job satisfaction. Meanwhile, the quality of work life contributes significantly positively to employee performance and job satisfaction. Apart from that, there is a significant favourable influence of job satisfaction on employee performance; then, there is a positive and significant influence of work stress and quality of work life on employee performance through the mediation of job satisfaction.Originality (Novelty) – Reveals previously unrevealed findings and comprehensively contributes to a theoretical and practical understanding of work behaviour and human resource development.Implications – Providing direction includes; developing stress management programs, improving the quality of work life, and strengthening job satisfaction to improve employee performance and welfare.